Debates in the Press Concerning Ruthenian National Ambitions and Assimilation to Hungarians at the Turn of the 19th and 20th Centuries - Csíki Tamás (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2021)
Abstract. At the end of the 19th century, the ideal of the Hungarian nation state and the programme of Magyarisation got into an ever deepening conflict with the cultural, national or political ambitions of the ethnic groups living in Hungary. The ambition of forming and strengthening the Ruthenian ethnic and cultural community was intertwined with creating the standardised language norm, with church schools and the teaching of the Ruthenian language, with the autonomy of the Greek Catholic church and the language of liturgy as well as with the protection of Cyrillic writing. In this paper, I am investigating debates in the press at the turn of the century concerning these questions, which provides information about ethnic minorities policy and the local responses to it, the ideological contexts of group formation and the ideas formed about the Ruthenian society in Subcarpathia. The linguistic analysis of the articles published in newspapers may also provide information about the authors’ identification as well as attitudes to the Ruthenian and Hungarian communities and to the state.

Резюме. Наприкінці XIX століття ідеал угорської національної держави та програма мадяризації вступили у більш поглиблений конфлікт з культурними, національними і політичними прагненнями етнічних груп, що проживали в Угорщині. Намагання створити та зміцнити русинську етнічну і культурну спільноту перепліталася зі створенням стандартизованої мовної норми, конфесійних шкіл, запровадженням викладання русинської мови, а також з автономією греко-католицької церкви, мовою літургії і захистом кириличного письма. У дослідженні представлено дебати стосовно цих питань у тогочасній пресі, яка публікувалася на рубежі століть і охоплювала інформацію про національну політику і реакцію на неї на місцевому рівні, про ідеологічні контексти формування груп та уявлення про русинське суспільство на Закарпатті. Лінгвістичний аналіз статей, опублікованих у газетах, також свідчить про ідентифікацію авторів, ставлення до русинської і угорської спільноти та держави.

A 19. század végén a magyar nemzetállam eszménye és a magyarosítás programja egyre mélyülő konfliktusba került a Magyarországon élő etnikai csoportok kulturális, nemzeti vagy politikai törekvéseivel. A ruszin etnikai, illetve kulturális közösség megteremtésének és megerősítésének ambíciója a standardizált nyelvi norma megalkotásával, a felekezeti iskolákkal és a rutén nyelv oktatásával, a görögkatolikus egyház autonómiájával és a liturgia nyelvével, valamint a cirill betűs írás védelmével fonódott össze. A tanulmányban az ezekről a kérdésekről a századfordulón folytatott sajtóvitákat mutatom be, melyek a nemzetiségpolitikáról és a rá adott lokális válaszokról, a csoportképződés ideológiai kontextusairól, valamint a kárpátaljai ruszin társadalomról alkotott képzetekről tájékoztatnak. Az újságokban megjelenő cikkek nyelvi vizsgálata a szerzők identifikációjáról, a ruszin és a magyar közösséghez, illetve az államhoz kapcsolódó attitűdökről is tanúskodnak.
A ruszin nemzeti törekvések és a magyarosodás publicisztikai vitái a 19–20. század fordulóján
Публіцистичні дебати щодо національних прагнень русинів і мадяризація на рубежі ХІХ–ХХ століть
https://kmf.uz.ua/wp-content/uploads/2022/04/limes-2021-issue-viii_2021-12-30.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00009320
Keywords: Rusyns; Magyarisation; acculturation; Greek Catholic church; publicism